The interleukin 1 inhibitor canakinumab in the treatment of cryopyrin-associated periodic syndromes (CAPS): clinical experience - Svetlana Olegovna Salugina; E. S. Fedorov; N. N. Kuzmina; E. Yu. Zakharova (Современная ревматология)
Interleukin (IL) 1βis a major mediator of cryopyrin-associated periodic syndrome (CAPS). In this connection, the experience with IL-1 inhibitors used in patents with CAPS is being accumulated worldwide. Canakinumab was approved by FDA and EMEA in 2009 to treat CAPS and registered in the Russian Federation for this in 2011. The drug has been shown to be highly effective and well tolerated by patients with CAPS.Objective: to present Russia's experience in using the IL-1 inhibitor canakinumab in children with CAPS.Subjects and methods. The trial enrolled 6 CAPS patients, including 4 with Muckle-Wells Syndrome (MWS) and 4 with chronic infantile onset neurologic cutaneous articular/neonatal onset multisystem inflammatory disease (CINCA/NOMID), among whom there were 5 female patients aged 3.5 to 40 years and 1 male patient aged 17 years. Two patients (a 17-year-old daughter and her 40-year-old mother) were stated to have a familial MWS case. The duration of the disease was 3.5 to 33 years. All the patients underwent a molecular genetic analysis for mutations in the NLRP3 (CIAS1) gene. Four patients with MWS were found to have Thr436Ile and Thr438Ile mutations; the mother and her daughter had Thr350Met mutations; no mutations were detected in 2 patients with CINCA/NOMID. At the study, one female patient with MWS took gluco-corticoids (GC) in a dose of 0.1 mg/kg; the others received symptomatic therapy with nonsteroidal antiinflammatory drugs. Canakinumab was injected subcutaneously every 8 weeks in a dose of 4 mg/kg for patients with a body weight of <15 kg and in a dose of 2 mg/kg for those with a body weight of >15 kg. By now, 2 patients with MWS received 7 injections of the drug (a 48-week follow-up); 2 patients with CINCA/NOMID had its 6 injections (a 40-week follow-up) and 2 patients with MWS had 2 injections (a 10-week follow-up).Results. All the patients showed a significant clinical improvement: recovery; elimination of fever, rash, and eye symptoms; and a reduction in the levels of acute-phase markers. The effect retained throughout the follow-up. GC could be completely discontinued in the female patient with MWS. No adverse events were observed in any case.Conclusion. The experience in using canakinumab in the patients with CAPS showed the high efficacy and good tolerability of the drug. The decrease in acute-phase markers was slower in the patients with CINCA/NOMID, the most severe form of CAPS.